Adaptable modular construction systems and multi-objective optimisation strategies for mass-customised housing: A new user-driven paradigm for high-rise living in Hong Kong. (March 2022) - Ma, Chun Yu; van Ameijde, Jeroen
There has been a recent increase in the exploration of 'the discrete' in architecture, speculating on how an integrated approach to design, fabrication, assembly and inhabitation can disrupt the traditional investment- and decision-making models in the housing industry. Strategically designed part-to-whole systems allow for differentiation and reconfiguration, and the incorporation of different end-user' requirements. This potential of 'democratising' housing production requires further research into how the negotiation between multiple stakeholders' preferences can be guided through digital methods. This paper presents a research-by-design project that applies a digital and discrete material system to high-rise housing in Hong Kong, a typology which often features high degrees of standardisation. Through the development of an adaptable modular construction system and a multi-objective optimisation workflow, a system is explored that addresses the challenges of high-rise construction, and of customising high-density housing. The case study project demonstrates the ability of the workflow's evolutionary algorithm to balance complex requirements including maximising views, daylight access and internal connectivity according to diverse user requirements.